COMMUNICATION STRATEGIES IN A CASUAL CONVERSATION, the Case of the First Year Students of Semarang State Polytechnic - Jozef Bambang Tri Joga (Dinamika Bahasa dan Budaya, 2014)
This study aimed at listing the communication strategies applied by Semarang State Polytechnic students sitting in the first year of Business Administration Department in a recorded natural conversation with a native-like speaker.  Through the research question of “what communication strategies do the Polytechnic students use in a casual conversation?”, and using the nine criteria such as paraphrasing, borrowing, and avoiding and  six other criteria of communication strategies, this study evaluated the strategies used to keep a casual conversation run well.  The recorded data were transcribed using ordinary orthography, analyzed and identified what communication strategies were used, then, explained the reason for using them. The result showed that Non Native Speaker managed to carry out a casual chatting, even though it jumped from one topic to another, due to no special topics provided.  Grammatical errors were occasionally made, however, they didn’t hamper the flow of the conversation. The Native-Like Speaker was often found lowering the level of difficulty by slowing the speed of speaking, repeated words with the synonym, and uttering items with considerable clarity. Key words: communication strategies, casual communication, flow of communication.